2018
DOI: 10.1111/tan.13403
|View full text |Cite
|
Sign up to set email alerts
|

Improved flow cytometry crossmatching in kidney transplantation

Abstract: Flow cytometry crossmatching (FC‐XM) assay is the most sensitive cell‐based method for detecting donor‐specific antibodies (DSAs). However, the use of FC‐XM remains limited by methodological and clinical variations. This basic assay cannot discriminate between complement‐fixing and noncomplement‐fixing antibodies. FC‐XM also detects patient all antibodies bound to donor cells and not only DSAs against to HLA molecules. Pretest factors associated with a donor's medical care can affect test results by changing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Lymphocytes express many surface antigens besides HLA molecules, and some of these antigens can bind antibodies circulating in the recipient's serum, irrespective of their specificity. [11] In FCXM have been described different causes of false-negative results, including: (a) low levels of HLA expression on donor cells, (b) excess number of cells, (c) low serum volume (which is generally a bad cell-to-antibody ratio), (d) low DSA levels, (e) low purity of the lymphocytes, and (f) high background in the negative control serum. False-positive results may be due to: (a) IgG binding to FcR in B cells, (b) low background in the negative control, (c) insufficient washing after incubations with antibodies, (d) autoantibodies, and (e) the use of therapeutic antibodies such as anti-thymocyte globulin, rituximab (anti-CD20), alemtuzumab (anti-CD52), basiliximab (anti-CD25), and daclizumab (anti-CD25).…”
Section: Flow Cytometry Crossmatch: Enhancing Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphocytes express many surface antigens besides HLA molecules, and some of these antigens can bind antibodies circulating in the recipient's serum, irrespective of their specificity. [11] In FCXM have been described different causes of false-negative results, including: (a) low levels of HLA expression on donor cells, (b) excess number of cells, (c) low serum volume (which is generally a bad cell-to-antibody ratio), (d) low DSA levels, (e) low purity of the lymphocytes, and (f) high background in the negative control serum. False-positive results may be due to: (a) IgG binding to FcR in B cells, (b) low background in the negative control, (c) insufficient washing after incubations with antibodies, (d) autoantibodies, and (e) the use of therapeutic antibodies such as anti-thymocyte globulin, rituximab (anti-CD20), alemtuzumab (anti-CD52), basiliximab (anti-CD25), and daclizumab (anti-CD25).…”
Section: Flow Cytometry Crossmatch: Enhancing Sensitivitymentioning
confidence: 99%
“…False-positive results may be due to: (a) IgG binding to FcR in B cells, (b) low background in the negative control, (c) insufficient washing after incubations with antibodies, (d) autoantibodies, and (e) the use of therapeutic antibodies such as anti-thymocyte globulin, rituximab (anti-CD20), alemtuzumab (anti-CD52), basiliximab (anti-CD25), and daclizumab (anti-CD25). [10,11] Correlating crossmatch results with patient history, sensitizing events, and DSA history is important when interpreting possible false-positive or false-negative scenarios. Therefore, an adequate analysis will allow us to define if they are DSAs and, therefore, a more precise immunological risk based on the FCXM.…”
Section: Flow Cytometry Crossmatch: Enhancing Sensitivitymentioning
confidence: 99%
“…As a significant proportion of patients reportedly presented an uneventful clinical course, although they were FCXM-positive, FCXM is considered a test with high sensitivity and low specificity in early graft dysfunction and antibody-mediated rejection (ABMR) [ 23 ]. Furthermore, FCXM can be impacted by several variable factors, including flow cytometers, fluorochrome reagents, cell-to-serum ratio, and incubation conditions, rendering standardization difficult.…”
Section: Alloantibody Detectionmentioning
confidence: 99%
“…It is necessary to establish individual cutoff values for each laboratory [ 24 ]. Moreover, the problem of false positives induced by non-HLA antibodies, autoantibodies, and rituximab tends to persist, which are disadvantages associated with traditional CDC crossmatch [ 23 ].…”
Section: Alloantibody Detectionmentioning
confidence: 99%
“…In a landmark publication, Patel and Terasaki reported that 24 of 30 kidneys transplants performed across a positive complement dependent cytotoxicity crossmatch (CDC-XM) failed in an accelerated fashion 1 . Test systems to detect circulating antibodies at a higher sensitivity than CDC-XM have been developed, and the flow cytometry crossmatch (FCXM) is in widespread use to identify donor specific IgG antibodies (DSA) [2][3][4][5] . Pre-transplant FCXM results are used in many centers for optimizing donor selection, and pre-transplant T and B cell FCXM results have been associated with allograft outcomes [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%